Study of Plankton diversity status of local habitat in eastern Uttar Pradesh - Ankita Sahu; Ram P Yadav; Ajay Singh (Annals of Limnology and Oceanography - Peertechz Publications, 2021)
The studies included the local habitat of Lake River and ponds, which are most important, share the habitat in local flora and fauna in eastern Uttar Pradesh (U.P.) India. The study was conducted to assess the mainly phytoplankton and zooplankton status of the Ramgarh lake, Maheshra tal, and Rapti river in Gorakhpur district of Uttar Pradesh, India by examining the biological parameters. The most important planktonic group encountered in the present study was cyanophyceae and Zygnematophyceae Nostocale and Desimidiale encountered as other genera which existed in the Ramgarh lake, Maheshra tal, and Rapti river water of the habitat. The study found that the members of protozoans group animal contribute 50 percent of the total zooplankton population during the year of the study period.